Assessing the determinant factors affecting green entrepreneurial intention among female entrepreneurs in Indonesia - Ninik Sri Rahayu (Cogent Business & Management, 2024)
Women have been identified as critical actors for sustainable entrepreneurship. This study aims to assess women's ecopreneur intentions by employing the theory of planned behavior. Survey data was collected from 158 females in Indonesia's small and medium enterprises (SMEs) sector. The results of partial least square-structural equation modeling (PLS-SEM) revealed that self-efficacy and environmental awareness positively impact sustainable entrepreneurial inclinations. Aside from this, these findings indicate that green entrepreneurial motivation plays a vital role in mediating the relationship between self-efficacy, ecological awareness, and the tendency to develop environmentally friendly enterprises. Surrounded by the COVID-19 outbreak, this study implied that the pandemic significantly influences green entrepreneurship self-efficacy and natural consciousness among businesswomen. The results of studies advance the academic debate on the contribution of women in inclusive and sustainable development. Further, it could assist planners and policymakers in strengthening women entrepreneurs' sustainable business models that allow them to capture opportunities and shape their post-pandemic futures.
Keywords: 650; Women entrepreneurs; post-covid-19; self-efficacy; ecological consciences; green entrepreneurial intentions